2023
DOI: 10.1021/acs.jmedchem.2c01753
|View full text |Cite
|
Sign up to set email alerts
|

Application and Study of ROCK Inhibitors in Pulmonary Fibrosis: Recent Developments and Future Perspectives

Abstract: Rho-associated coiled-coil-containing kinases (ROCKs), serine/threonine protein kinases, were initially identified as downstream targets of the small GTP-binding protein Rho. Pulmonary fibrosis (PF) is a lethal disease with limited therapeutic options and a particularly poor prognosis. Interestingly, ROCK activation has been demonstrated in PF patients and in animal PF models, making it a promising target for PF treatment. Many ROCK inhibitors have been discovered, and four of these have been approved for clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 157 publications
0
5
0
Order By: Relevance
“…Rac1 activation facilitates the formation of precursor adhesions [46], while Cdc42 stimulation leads to the development of filopodia with parallelarranged actin filament bundles [47]. RhoA activation is associated with the formation of actin stress fibers and mature focal adhesions [48]. Therefore, we speculate that these signaling molecules may be involved in the mechanisms by which cell invasion is inhibited and cell migration is promoted upon the reduction HtrA4.…”
Section: Discussionmentioning
confidence: 93%
“…Rac1 activation facilitates the formation of precursor adhesions [46], while Cdc42 stimulation leads to the development of filopodia with parallelarranged actin filament bundles [47]. RhoA activation is associated with the formation of actin stress fibers and mature focal adhesions [48]. Therefore, we speculate that these signaling molecules may be involved in the mechanisms by which cell invasion is inhibited and cell migration is promoted upon the reduction HtrA4.…”
Section: Discussionmentioning
confidence: 93%
“…32 Over two decades of development, the structural diversity of ROCK inhibitors has been extensively explored, encompassing isoquinoline/isoquinolinone, indazole, pyridine, pyrimidine, pyrazole, aminofurazane, and boron derivatives. 33,34 To date, four ROCK inhibitors have received regulatory approval and are commercially available. Additionally, several others are currently in various stages of clinical trials (Figure S1).…”
Section: ■ Introductionmentioning
confidence: 99%
“…Recent studies have shown that the overactivation of ROCK kinases also occurs in the pathological processes of autoimmune-related diseases such as systemic lupus erythematosus, rheumatoid arthritis, inflammatory bowel disease, and psoriasis . Over two decades of development, the structural diversity of ROCK inhibitors has been extensively explored, encompassing isoquinoline/isoquinolinone, indazole, pyridine, pyrimidine, pyrazole, aminofurazane, and boron derivatives. , To date, four ROCK inhibitors have received regulatory approval and are commercially available. Additionally, several others are currently in various stages of clinical trials (Figure S1).…”
Section: Introductionmentioning
confidence: 99%
“…Isoquinolines, an important class of nitrogen-containing heterocycles, which possess diverse biological activity and are widely found in numerous natural products such as isoquinoline alkaloids . For example, Berberine exhibits anti-inflammatory activity, Papaverine has antispasmodic activity, and Corydamine analogue shows anticancer activity (Figure ).…”
mentioning
confidence: 99%